2021
DOI: 10.3390/coatings11020204
|View full text |Cite
|
Sign up to set email alerts
|

Implantable Thin Film Devices as Brain-Computer Interfaces: Recent Advances in Design and Fabrication Approaches

Abstract: Remarkable progress has been made in the high resolution, biocompatibility, durability and stretchability for the implantable brain-computer interface (BCI) in the last decades. Due to the inevitable damage of brain tissue caused by traditional rigid devices, the thin film devices are developing rapidly and attracting considerable attention, with continuous progress in flexible materials and non-silicon micro/nano fabrication methods. Therefore, it is necessary to systematically summarize the recent developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 117 publications
(186 reference statements)
0
5
0
Order By: Relevance
“…Recently, excellent progress has been achieved toward developing implantable miniature wireless ES devices ( 64 ). Furthermore, the development of soft and electroactive biomaterials has reduced the physical mismatch at the tissue-device boundary ( 65 ), thereby making long-term electroceutical treatment more viable. It should be noted that ES devices have been considerably developed toward neuromodulation, and skeletal muscle stimulation has received relatively less attention.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, excellent progress has been achieved toward developing implantable miniature wireless ES devices ( 64 ). Furthermore, the development of soft and electroactive biomaterials has reduced the physical mismatch at the tissue-device boundary ( 65 ), thereby making long-term electroceutical treatment more viable. It should be noted that ES devices have been considerably developed toward neuromodulation, and skeletal muscle stimulation has received relatively less attention.…”
Section: Discussionmentioning
confidence: 99%
“…It was gradually discovered that electrical stimulation of damaged neural tissue causes deep cellular alterations associated with regeneration and repair. 8,83 Research with in vitro and in vivo models has confirmed that the depolarizing current applied to the site of the damaged axon has a significant effect on axon germination and regeneration. 84 In this regard, functional hydrogels have become promising bioelectronics and biomedical engineering candidates, with more focus dedicated to solving neurological problems.…”
Section: Conductive Hydrogel-based Neural Interfacesmentioning
confidence: 99%
“…b) Reproduced under the terms of the CC‐BY Creative Commons Attribution 4.0 International license (https://creativecommons.org/licenses/by/4.0). [ 204 ] Copyright 2021, The Authors, published by MDPI. c) Reproduced with permission from Mark Stone/University of Washington.…”
Section: Surface Electrode Arrays For the Central And Peripheral Nerv...mentioning
confidence: 99%